Have health inequities, the COVID-19 pandemic and climate change led to the deadliest heatwave in France since 2003?. (May 2021) - Pascal, M.; Lagarrigue, R.; Laaidi, K.; Boulanger, G.; Denys, S.
Abstract: Objectives: Between 2015 and 2019, 5700 excess deaths were observed during heatwaves in France. The summer of 2020 combined exceptionally high temperatures with the COVID-19 pandemic. The associated health impacts of this unique situation are described in this study. Study design: This is an observational study based on indicators of the French heat prevention plan. Methods: Mortality and morbidity data during heatwaves were compared between 2020 and previous years, alongside COVID-19 in-hospital mortality. Results: In total, 1921 additional deaths (+18.2%) were observed during the 2020 heatwaves, which is the largest number of deaths observed since 2003. Less than 100 deaths were attributed to COVID-19 during the heatwaves of 2020. Conclusions: Exceptionally high temperatures driven by climate change, combined with health inequities exacerbated by the COVID-19 outbreak, may have increased vulnerability to heat in 2020.